Giant retroperitoneal lipoma - Kansakar, P; Ghimire, B; Rajbhandary, A; C, HK; Singh, YP; Vaidya, P (Journal of Institute of Medicine Nepal, 2008)
Case report: This is a case report of a retroperitoneal lipoma.The patient was admitted with complaints of abdominal distention and early satiety. Contrast enhanced CT scan of abdomen showed a large mass of fat density arising from the retroperitoneum measuring 30 x 25 x 20cm displacing the left kidney towards the midline and anteriorly. Fat plane was maintained with surrounding structures. The patient underwent exploratory laparotomy and the lipoma was excised. The lesion measured 30 x 20 cm and weighed 5.1 kgs. Since the left kidney was displaced anteriorly and towards the midline, nephropexy was performed. Histopathology revealed benign lipoma. Post operative period was uneventful. Key words: Lipoma, retroperitoneal mass, displaced kidney. The full text of this paper is available at Journal of Institute of Medicine website